Ski boots for children (6 to 12 years - beginner and intermediate level) - problem areas and kinesic behavior - Kogler, H.; Müller, E. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Ski boots for children (level beginner and intermediate) between the age of 6 and 12 cause problem zones, usually pressure marks, due to the ongoing growth of a child's foot. These areas prevent the right movement of the feet. A child's movement has to be taken into consideration whilst the design and the development of a childrens ski boot.